Mengenali Dampak Kehamilan Dini Pada Remaja di Madrasah Aliyah Negeri Banda Kabupaten Maluku Tengah - Dewi Arwini Bugis; Petriana Ekklesia Mahmud (Universitas Muhammadiyah Manado, 2023)
The lack of open communication within the family, both from parents and children, indirectly facilitates deviant behavior in adolescents, especially in the case of premarital sex. One of the consequences of this behavior is an unwanted pregnancy (KTD). Pregnancy under the age of 20 has a significant impact on increasing maternal mortality, both in Indonesia and worldwide. Through this community service activity, it aims to increase adolescents' understanding of premarital sex by involving a total of 40 respondents. Evaluation during this activity showed that all respondents understood the counseling material. With this counseling program, it is hoped that students can increase their understanding of the effects of pregnancy and take preventive steps to avoid pregnancy.